Phenological behavior of feijoa accessions in their main diversity center - Sánchez-Mora, Fernando David; Saifert, Luciano; Ciotta, Marlise Nara; Ribeiro, Humberto Nunes; Malinovski, Luciane Isabel; Santos, Karine Louise dos; Ducroquet, Jean Pierre Henri Joseph; Nodari, Rubens Onofre (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to identify the minimum base temperature (Tb) and the maximum base temperature (TB) to predict the thermal time for six phenological stages of feijoa (Acca sellowiana) accessions. During ten noncontinuous harvests (2004 to 2017), 247 feijoa accessions, maintained in the Feijoa Active Germplasm Bank, in São Joaquim, in the state of Santa Catarina, Brazil, had their data recorded for: initial sprouting (IS), initial flowering (IF), end of flowering (EF), beginning of harvest (BH), and end of harvest (EH). Tb and TB were estimated by the Arnold’s method of least variability, and the TT requirements were obtained by Ometto’s method. Tb at 7.76°C and TB at 17.0°C were necessary when feijoa plants started growing (IS stage) just after winter; and Tb at 10.6°C and TB at 19.5°C were the calculated values from IS until BH. The budding stage of the accessions began in the mid-September (50.6%); flowering occurred predominantly in November (90%); and harvest began in March and lasted until May. About 176 days, with 1,014.4 growing degree-days, are necessary to complete the productive cycle from IS until BH. The early, intermediary, and late fruit-ripening accessions show different thermal time requirements.
Keywords: Acca sellowiana; base temperature; growing degree-days; pineapple guava; thermal time